The relationship between corporate governance and stock liquidity in Palestine and Jordan stock markets: the mediating effect of leverage - Omari, Ahmed (جامعة النجاح الوطنية, 2019)
This study aims to examine the influence of some corporate governance mechanisms (board size, board independence, chief executive officer duality, gender diversity in the board, and insider share ownership) on stock liquidity with mediating effect of financial leverage among 244 listed firms in Palestine stock exchange and Amman stock market during 2006 to 2017. The study examined three main hypotheses. The first hypothesis examined the influence of corporate governance mechanisms on stock liquidity, and outcomes of the study revealed that the relationship between female on board and stock liquidity is positive and insignificant. Furthermore, there is a positive and insignificant relationship between chief executive officer duality and stock liquidity. Additionally, there is a positive and insignificant association among inside ownership and stock liquidity. However, the association among board size and stock liquidity is negative and significant. Also, there is an inverse and insignifcant relationship between board independence and stock liquidity. The second hypothesis examined the relationship between corporate governance mechanisms and financial leverage, and findings of the study indicate that there is a positive relationship between board size, female on board, and inside ownership with financial leverage. Whereas, an inverse relationship has been found between board independence, and chief executive officer duality with financial leverage. The third hypothesis examined the association between financial leverage and stock liquidity, and outcomes of the study revealed that there is an inverse and significant association between level of financial leverage and stock liquidity
العلاقة بين حوكمة الشركات وسيولة الاسهم في سوقي فلسطين والاردن: الرفع المالي كمتغير وسيط